Kualitas Hidup Peserta Prolanis Diabetes Melitus Tipe 2 dengan Instrumen Dqol-BCI di Wilayah Kerja Puskesmas Mokoau Kendari - Hilda Harun; Paridah Paridah (KOLONI, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic disease that significantly impacts patients' quality of life, particularly among participants of the Chronic Disease Management Program (Prolanis) in primary healthcare facilities. Quality of life is an important indicator in evaluating the success of comprehensive chronic disease management. This study aimed to describe the quality of life of T2DM Prolanis participants at Puskesmas Mokoau, Kendari City, using the Diabetes Quality of Life Brief Clinical Inventory (DQoL-BCI) instrument. This was a descriptive quantitative study with a cross-sectional approach. The population consisted of all T2DM Prolanis participants in the working area of Puskesmas Mokoau, Kendari City, Southeast Sulawesi Province. Total sampling was employed, where all T2DM Prolanis participants who met the inclusion criteria were included as respondents, totaling 35 participants. Quality of life was measured using the DQoL-BCI instrument (Burroughs, 2004) comprising 15 items on a 1–5 Likert scale. Data were analyzed using univariate analysis including frequency distribution, mean, and standard deviation. Most respondents were aged 61–72 years (60.0%), female (57.1%), educated at diploma/bachelor level (68.6%), and had been diagnosed with DM for 1–2 years (60.0%). The quality of life of T2DM Prolanis participants showed that 48.6% had good quality of life, 25.7% moderate, and 25.7% poor, with a mean score of 55.63 ± 15.14. Nearly half of T2DM Prolanis participants had good quality of life; however, a significant proportion with moderate and poor quality of life requires further attention and intervention.